Economic issues in a community immigration policy: the regional dimension - Roger Vickerman (European Regional Science Association (ERSA), 2002)
In November 2000 the European Commission published its communication "On a Community Immigration Policy". The Commission's Document identifies clearly the changing pressures which have affected the need for a reappraisal of immigration policy. First, the advent of the single market with free movement of labour within the EU requires a common approach to immigration over the EU's external borders. Secondly, the gradual transition from an era of high unemployment into one of tighter labour markets, coupled with demographic change, has been revealing increasing problems of labour market bottlenecks, especially in respect of certain specific skills, requiring more than a national-based competitive bidding for selected immigrants. Thirdly, there has been an increase in asylum-seeking and illegal migration. The particular pressure for a review of EU policy on immigration has come from the situation in Central and Eastern Europe over the past decade, in particular how to accommodate the accession of the first waves of candidate countries into a unified single labour market and how to regulate the anticipated continuing pressure for migration from those countries in the region remaining outside the EU. The enormous increase in migration activity in the early 1990s, following a long period of stable or falling migration pressure since the 1950s and early 1960s, demonstrated both types of migration, genuine pressures for workers to migrate from poor regions to rich regions as part of an increasing integration of the European economy and large flows of population resulting from war and ethnic conflict. Although it is easy to demonstrate that the overall pressure of immigration to the EU is not likely to be great, there is the problem that such immigration is highly regionally concentrated and this has implications both for the policy as a whole and for regional development within the EU. This paper assess the regional impacts of migration in the context of a model of migration which stresses the limited duration of much migrant activity. It highlights the importance of short-term migration in terms of remittances and productivity gain, but identifies the importance of improving information to reduce the asymmetry which lead to mismatch and hence to reduced welfare in both sending and receiving regions. Particular evidence is drawn from data on migration from Poland, Albania and Bulgaria. The paper concludes that Immigration Policy needs to address mechanisms for identifying migrant flows and preparing for their easy absorption. Rather than trying to set aggregate quotas or optimal transition periods to free movement; this may be most efficiently achieved through use of voucher or auction systems.
Keywords: 330